A capacitive humidity sensor based on all-protein embedded with gold nanoparticles @ carbon composite for human respiration detection. (19th February 2021) - Ma, Liyun; Patil, Aniruddha; Wu, Ronghui; Zhang, Yifan; Meng, Zhaohui; Zhang, Wenli; Kong, Lingqing; Liu, Xiang Yang; Wang, Jun
Abstract: Wool and silk fiber are the most extensive resources of protein fibers and have been used in the textile field for many years. The extracted biocompatible proteins are more and more widely used in flexible devices, sensors, tissue engineering, etc. Here, a fully biomaterial based flexible humidity sensor has been successfully fabricated for the first time. Interdigital electrodes of humidity sensor are printed on a transparent sensor substrate made of silk protein by inkjet printing. The humidity sensitive material is gold nanoparticles hosted nitrogen doped carbon (AuNPs@NC), which is fabricated by in situ dispersion of gold nanoparticles in a wool keratin assisted porous carbon precursor. The best treatment condition of the sensitive materials is obtained by comparing the sensitivity of humidity response. Moreover, the as-prepared biocompatible flexible sensor was successfully used to detect human respiration.